Cytological diagnosis of glandular lesions of the cervix - O. G. Grigoruk; T. A. Moskvina; L. M. Bazulina; I. V. Vikhlaynov (Опухоли женской репродуктивной системы, 2025)
Background. The reproducibility of cytomorphological abnormalities results of the glandular epithelium of the cervix between cytopathologists is low.Aim. To evaluate the lesions of the glandular epithelium in the cervix according to the Bethesda system in the practicing cytological work.Materials and methods. In a retrospective study, a comparative analysis of cytological cervical smears with abnormal changes in the glandular epithelium was performed. The evaluation of cytological material was carried out in accordance with the Bethesda system (2014). For the analysis, we used information about 112 patients from the cancer registry of the Altai Regional Oncology Dispensary (Barnaul) for 2023. In some cases, liquid-based cytology (ThinPrep™ Processor (Hologic)) was used. The preparations were stained using Papanicolaou, Pappenheim and hematoxylin-eosin tests. When assessing the effectiveness of cytological diagnostics, the results of histological studies were used taking into consideration clinical and anamnestic information.Results. The studied cytograms of patients with glandular cell abnormalities were divided into groups: atypical glandular cells, not otherwise specified (n = 19 (0.13 %)); atypical glandular cells suspicious for adenocarcinoma (or favor for neoplastic) (n = 9 (0.06 %)); endocervical adenocarcinoma in situ (n = 4 (0.03 %)); adenocarcinoma (n = 80 (0.54 %)). Conclusion. Cytological diagnosis of glandular lesions of the cervical canal is crucial for subsequent colposcopy and obtaining biomaterial for intravital histological examination. When determining whether cells belong to the “Atypical glandular cells” group, there is a large differential range of different diseases. These cases provide future outlook for further improvement of cytological diagnostics. In the group of patients “Atypical glandular cells suspicious for adenocarcinoma”, endometrial adenocarcinoma was subsequently diagnosed in 88.89 %. The proportion of correct cytological diagnosis in the 2 described groups was 91.94 %. In observations of endocervical adenocarcinoma in situ, cellular elements in cytological preparations characterized adenocarcinoma. All diagnosed adenocarcinomas – endocervical, endometrial and various internal organs of the woman’s body – were identified during subsequent histological examination. Adenocarcinoma accounted for 24.02 % of the number of cervical carcinomas diagnosed cytologically during the year.